2000
DOI: 10.1002/1097-4636(20001215)52:4<797::aid-jbm25>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to sliding of orthodontic appliances in the dry and wet states: Influence of archwire alloy, interbracket distance, and bracket engagement

Abstract: Having established dimensional and mechanical characteristics, the resistances to sliding (RS) were measured in vitro for various archwires against stainless steel brackets. Using stainless steel ligatures, a constant normal force (300g) was maintained while second-order angulation (straight theta) was varied from -12 degrees to +12 degrees. Using miniature bearings to simulate contiguous teeth, five experiments each were run in the dry or wet states with human saliva at 34 degrees C as a function of four arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 21 publications
4
32
0
2
Order By: Relevance
“…Furthermore, it has been found that short-term temperature changes can affect the stiffness of an archwire, 21,22 which is correlated with friction and binding. 15,23,24 However, no studies have been conducted on the effect of oral temperature changes with respect to friction. The aims of the study were to investigate the influence of bracket bevel design and oral environment on frictional resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been found that short-term temperature changes can affect the stiffness of an archwire, 21,22 which is correlated with friction and binding. 15,23,24 However, no studies have been conducted on the effect of oral temperature changes with respect to friction. The aims of the study were to investigate the influence of bracket bevel design and oral environment on frictional resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A range of techniques have been used to examine the lubricating properties of saliva and its components, including atomic force microscopy (AFM) [41][42][43] and simple tribometers [21,23,[44][45][46][47][48][49]. These studies primarily focus on the influence of saliva, the acquired pellicle (a proteinacious layer on the enamel surface) and saliva substitutes on the tribological properties of enamel/teeth surfaces and orthodontic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of saliva appears to have no significant influence on the reduction of frictional force. 17 The samples were analyzed after removal from the oral environment, which may have caused drying of the residues on the orthodontic wire surfaces. However, this drying may also occur during clinical use, when they remain in the oral cavity for months.…”
mentioning
confidence: 99%